Billion-dollar ransom : a thriller [large type] - Patterson, James, 1947-; Swierczynski, Duane (Little Brown and Company, 2025)
Five members of a billionaire's family. In different locations. All kidnapped at the same moment. Two children taken from a private-school bus. A film producer and a movie star grabbed at a hideaway resort. A beautiful wife whisked off the streets of Beverly Hills. A patriarch wants his family back. The cash, gold, jewels, are crypto are all ready. There's only one problem: a brilliant, very stubborn FBI agent. Special Agent Nicky Gordon doesn't want to pay the kidnappers. Not a dime.--